The Light and Shadow of Senescence and Inflammation in Cardiovascular Pathology and Regenerative Medicine - Iop, Laura; Dal Sasso, Eleonora; Schirone, Leonardo; Forte, Maurizio; Peruzzi, Mariangela; Cavarretta, Elena; Palmerio, Silvia; Gerosa, Gino; Sciarretta, Sebastiano; Frati, Giacomo (Mediators of Inflammation, 2017)
Recent epidemiologic studies evidence a dramatic increase of cardiovascular diseases, especially associated with the aging of the world population. During aging, the progressive impairment of the cardiovascular functions results from the compromised tissue abilities to protect the heart against stress. At the molecular level, in fact, a gradual weakening of the cellular processes regulating cardiovascular homeostasis occurs in aging cells. Atherosclerosis and heart failure are particularly correlated with aging-related cardiovascular senescence, that is, the inability of cells to progress in the mitotic program until completion of cytokinesis. In this review, we explore the intrinsic and extrinsic causes of cellular senescence and their role in the onset of these cardiovascular pathologies. Additionally, we dissect the effects of aging on the cardiac endogenous and exogenous reservoirs of stem cells. Finally, we offer an overview on the strategies of regenerative medicine that have been advanced in the quest for heart rejuvenation.